Surface and deep conceptualizations of silence and voice paradoxes: An empirical analysis of women behavior at workplace - Asad Shahjehan (Taylor & Francis Group, 2016)
Although the phenomena of organizational silence (OS) and voice are widely observed in the organizations, there exists little empirical evidence regarding their surface and deep conceptualizations and/or multiple paradoxes associated with their interaction. The study aims to investigate the surface and deep conceptualizations of these paradoxes while presenting its theoretical and empirical rationale for the possible differences based on relationships with subdimension of counterproductive work behavior and organizational identification among women at workplace. A sample of 168 women academicians was collected from three universities at three different stages of their lifecycle. The results indicate that on surface OS and voice display similar direct and moderating relationships with CWB and OI, respectively. However, the analysis of deep conceptualization shows that motives behind the paradoxes of silence and voice play an important role in shaping their relationships; with prosocial motives being most influential. With an empirical analysis, the study highlights the motives of silence and voice paradoxes and introduces new avenues for studying the interaction of multiple paradoxes associated with work behaviors in organizations.